2015
DOI: 10.4049/jimmunol.1401459
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10 Triggers Early Microglial Activation in the Cuprizone Model

Abstract: A broad spectrum of diseases is characterized by myelin abnormalities and/or oligodendrocyte pathology. In most, if not all, of these diseases, early activation of microglia occurs. Our knowledge regarding the factors triggering early microglia activation is, however, incomplete. In this study, we used the cuprizone model to investigate the temporal and causal relationship of oligodendrocyte apoptosis and early microglia activation. Genome-wide gene expression studies revealed the induction of distinct chemoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 111 publications
8
83
0
Order By: Relevance
“…Infiltration of microglia/macrophages peaks at 4.5 weeks of CPZ intoxication as is mediated by the chemokines CCL2, CCL3, and CXCL10 (Clarner et al, 2015). However, to the best of our knowledge, no studies have addressed microglia/macrophage behavior in the chronic CPZ model utilized in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infiltration of microglia/macrophages peaks at 4.5 weeks of CPZ intoxication as is mediated by the chemokines CCL2, CCL3, and CXCL10 (Clarner et al, 2015). However, to the best of our knowledge, no studies have addressed microglia/macrophage behavior in the chronic CPZ model utilized in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Glia were also assessed, since CPZ induces astrocytosis and phagocyte infiltration at intervals shorter than the chronic model utilized in this study (Norkute et al, 2008; Skripuletz et al, 2013; Gudi et al, 2014; Praet et al, 2014; Clarner et al, 2015). In addition, both human postmortem tissue and animal models of seizure show reactive astrocytes, which exhibit increased expression of the intermediate filament glial fibrillary acidic protein (GFAP) and alteration of astrocyte channels, including the water channel aquaporin-4 (AQP4) and the inward rectifying potassium channel Kir4.1, both of which are central to epileptogenesis (Oberheim et al, 2008; Anderson and Rodriguez, 2011; Binder et al, 2012; de Lanerolle et al, 2012; Rodriguez-Cruces and Concha, 2015; Nwaobi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CXCL10 is a chemokine that can be produced by neurons, astrocytes, and oligodendrocytes (145) and binds the receptor CXCR3 on memory T cells and NK cells to induce their migration to the site of infection (146). Indeed, the NK-specific transcript, natural killer cell triggering receptor (NKTR), was upregulated 7 and 10 dpi (FC of 3 and 4, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activation of microglia and infiltration of macrophages into the brain are markedly increased during cuprizone intoxication (McMahon et al, 2002). Recently, it has been reported that microglial activation is significantly reduced in CXCL10-deficient mice treated with cuprizone, suggesting a pivotal role of CXCL10 in cuprizone-induced neuroinflammation and demyelination (Clarner et al, 2015). Similarly, IFN-g, IL-6, IL-8, CCL4, and CXCL10 were shown to be significantly increased in the CSF of ASD individuals (Vargas et al, 2005).…”
Section: Neuroinflammation In Social Cognitive Deficitsmentioning
confidence: 95%